PEMANFAATAN TEPUNG KULIT SINGKONG DALAM DIVERSIFIKASI OLAHAN BATTER - Anti Riyanti; Rosie Oktavia Puspita Rini (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2022)
This reseach aims to determine the making of bandros batter made from cassava peel and as a comparison is bandros batter made from rice flour. From the results of the study showed that the results of the taste of the batter from this skin flour were favored by the wider community. The content of nutritional value in batters made from cassava peel flour has a very high carbohydrate content. The research method used is the experimental method. The data testing method uses organoleptic tests that rely on the senses of touch, sight, smell, taste, and hearing to provide an assessment of the ingredients in the resulting product and the assessment aspects are aroma, taste, color, and texture. The panelists in this study were 20 panelists. The recipe used in the manufacture uses the author's recipe.